An Analysis of the Intertextuality of Nasikh wa Mansukh Between the Qur’an and Hadith: Epistemological Issues in the Formation of Islamic Law - Muhammad Idil Fitri; Rendy Shaputra; Supriadi Hamid; Amir Hamzah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the concept of nasikh wa mansukh between the Qur’an and Hadith with a focus on epistemological problems in the formulation of Islamic law. The debate regarding the possibility of Hadith abrogating the Qur’an reflects differences among scholars concerning textual authority, transmission validity, and methods of interpreting revelation. Some scholars accept the concept under the condition that the Hadith is mutawatir, while others reject it because the Qur’an is considered the highest source of Islamic law. This research employs a qualitative approach using library research methods. Data were collected from literature on Qur’anic studies, ushul fiqh, Hadith, and contemporary Islamic thought. The analysis applies descriptive-analytical, intertextual, and Islamic epistemological approaches. The findings show that the relationship between the Qur’an and Hadith in the concept of abrogation is influenced by differing epistemological paradigms. Scholars who accept abrogation emphasize the unity of revelation, while those who reject it emphasize differences in textual authority and validity. The study also finds that many claims of abrogation can be understood through textual harmonization, contextual legal interpretation, and maqashid al-shariah approaches without literal annulment of legal rulings. Therefore, the concept of nasikh wa mansukh should be understood contextually and integratively to remain relevant in contemporary Islamic legal methodology.